#10: Fever and neutropenia. 10 years surveillance in a pediatric Mexican hospital. (26th March 2021) - Sánchez-Medina, E; Reyes-Hernández, A; Severiano-Tellez, A
Abstract: Background: Fever and neutropenia, is a very common complication of chemotherapy in the treatment of cancer. It could happen in 10–50% of patients with solid tumors and more than 80% of patients with blood cancer. During leukemia treatment is very important first defense mechanisms integrity, such as skin, mucous membranes, Tlaxcala Children's Hospital is a pediatric general hospital, located in the center of Mexico and is where the pediatric cancer patients are treated, with almost 30 new cases by year, treatment with chemotherapy and as an adverse event fever and neutropenia, which increases morbidity and mortality Methods: We conducted an observational, descriptive, and analytic study aiming to identify fever and neutropenic events in ALL patients, their epidemiologic characteristics, antibiotic use, isolation and antibiogram, and outcome. Results: We reviewed 124 files from ALL patients between 2007–2017, we found 204 cases, 70 (33.8%) at induction, 18.6% consolidation, reinduction 17.6%, maintenance 14.2%. Out of 204 cases, we documented 177 with fever and neutropenia, 15 events of septic shock and 12 with fever and neutropenia with an identifiable source; the first-line antibiotic for fever and neutropenia was ceftazidime/amikacin, and for septic shock cefepime with an aminoglycoside, we found 3.39%, 20%, and 0% deaths from each group. Patients with fever and neutropenia with or without identifiable source had a length-stay average of 9.8 days compared with 30 days in patients with septic shock, CRP average was 12.47 mg/dL in the patients who survived and 8.23 mg/dL in those who did not. We found a very low positivity in cultures, and in most cases, those cultures did not meet criteria for diagnosis, the most common bacteria identified were E. coli, P. aeruginosa . Conclusions: This is the first approach to get a better knowledge about infectious complications in patients with ALL, these findings could lead to identifying opportunities to improve diagnosis and treatment which lead to reducing cost, morbidity, healthcare-associated infections.